Minimum Standards for Investment Performance: A New Perspective on Non-Life Insurer Solvency - Eling, Martin; Gatzert, Nadine; Schmeiser, Hato (Insurance Mathematics & Economics, 2009)
The aim of this paper is to develop an alternative approach for assessing an insurer's solvency as a proposal for a standard model for Solvency II. Instead of deriving minimum capital requirements-as is done in solvency regulation-our model provides company-specific minimum standards for risk and return of investment performance, given the distribution structure of liabilities and a predefined safety level. The idea behind this approach is that in a situation of weak solvency, an insurer's asset allocation can be adjusted much more easily in the short term than can, for example, claims cost distributions, operating expenses, or equity capital. Hence, instead of using separate models for capital regulation and solvency regulation-as is typically done in most insurance markets-our single model will reduce the complexity and costs for insurers as well as for regulators. In this paper, we first develop the model framework and second test its applicability using data from a German non-life insurer.
WiSo-Import:2015-03-26:957
Keywords: Kohäsion